Acceleration of Precarity: A Deleuzo-Guattarian Analysis of Novel Emancipation Strategies Within Cognitive Capitalism - Feichtinger, Michael (Momentum Quarterly, 2019)
Based on Gilles Deleuze’s and Félix Guattari’s deployment of Marx’s theory of capitalism in Thousand Plateaus, I show why certain strategies of resistance within the new paradigm of cognitive capitalism cannot be successful and highlight their shortcomings. Following that critique, I introduce Anna Tsing’s anthropological study on the matsutake pickers as a model of emancipation that maps possibilities for the transition to a post-capitalist society in hyper-precarious working conditions. I discuss the workers of Amazon’s Mechanical Turk as an equivalent of the matsutake pickers within the paradigm of cognitive capitalism as they construct their line of destruction as well. Finally, I argue that the left accelerationism consists in a radicalization of Tsing’s appeal of becoming-precarious that is hardly discussed in the theory itself. In the end I point out how this new and speculative emancipation strategies restore the possibility of thinking about the end of capitalism and a post-capitalist world.